10-Year Clinical Experience With 18F-Choline PET/CT: An Italian Multicenter Retrospective Assessment of 3343 Patients. (August 2020) - Zattoni, Fabio; Ravelli, Ilaria; Rensi, Marco; Capobianco, Decio; Borsatti, Eugenio; Baresic, Tania; Chiaravalloti, Agostino; Schillaci, Orazio; Alongi, Pierpaolo; Bartolotta, Tommaso Vincenzo; Rambaldi, Ilaria; Bartolomei, Mirco; et al.
Abstract : Purpose: The primary aim of this multicenter retrospective analysis is to examine the role of 18 F-choline PET/CT as a diagnostic tool for staging and restaging prostate cancer (PCa) in a large population in the light of 10 years of clinical experience. A secondary aim of the study is to produce data on the predictors of a positive 18 F-choline PET/CT result in the setting of PCa primaries and biochemical recurrences. Materials and Methods: This multicenter retrospective cohort study is based on data collected by 9 Italian nuclear medicine departments. Between October 2008 and September 2019, 3343 men underwent 18 F-choline PET/CT scans before receiving definitive treatments for a primary PCa or biochemical recurrence. Inclusion criteria were (1) histologically proven PCa (on surgical specimens or prostate biopsies from patients not treated surgically) and (2) availability of clinical and pathological data, including serum prostate specific antigen (PSA) level at the time of PET/CT scanning. Results: 18 F-choline PET/CT was performed in 545 cases (16.4%) for cancer staging and in 2798 (83.6%) for restaging purposes, and the result was positive in 540 (99.1%) for the former and 1993 (71.2%) for the latter. A positive PET/CT result was always associated with a high Gleason score (>7) and high PSA levels ( P < 0.01). The percentage of patients with a PSA threshold less than 1.0 ng/mL for performing PET/CT was higher in the years 2014 to 2019 (n = 341, 25% of cases) than during the previous period (n = 148, 16%; in 2008–2013). When used for staging purposes, receiver operating characteristic analysis showed that PSA levels of 9.2, 16.4, and 16.6 ng/mL were the optimal cutoffs for distinguishing between positive and negative PET/CT findings for local disease, lymph node involvement, and metastasis, respectively. In the restaging setting, a PSA level of 1.27 ng/mL was the optimal cutoff for distinguishing between a positive and negative PET/CT scan. Conclusions: 18 F-choline PET/CT can help identify early recurrences, even in the case of low PSA levels (<1 ng/mL). Our data suggest that important improvements have been made in the interpretation of 18 F-choline images and in patient selection in the last 5 years. Abstract : Supplemental digital content is available in the text.